2020
DOI: 10.1016/j.heliyon.2020.e03927
|View full text |Cite
|
Sign up to set email alerts
|

Childhood experiences and adult health: the moderating effects of temperament

Abstract: Existing literature demonstrates a strong relationship between childhood experiences and adult health outcomes. The Differential Susceptibility to Environment Theory suggests that there are several factors, including personality, that affect a child's sensitivity to adverse and advantageous experiences. A sample of 246 adults (ages 19-57) were asked questions about extroverted personality characteristics, adverse and advantageous childhood experiences (ACEs and counter-ACEs), and several indicators of adult he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…Zhu et al (2023) also found that higher parental PCEs predicted lower difficulties and prosocial problems in their children. Higher PCEs predicted less perceived stress, even after accounting for childhood adversity (Crandall et al, 2019;Doom et al, 2021;Miller et al, 2020;Novilla et al, 2022). While Narayan et al (2018) found that higher PCEs predicted less perceived stress during pregnancy, this relation became null after controlling for adversity.…”
Section: Mental Health Outcomesmentioning
confidence: 91%
See 1 more Smart Citation
“…Zhu et al (2023) also found that higher parental PCEs predicted lower difficulties and prosocial problems in their children. Higher PCEs predicted less perceived stress, even after accounting for childhood adversity (Crandall et al, 2019;Doom et al, 2021;Miller et al, 2020;Novilla et al, 2022). While Narayan et al (2018) found that higher PCEs predicted less perceived stress during pregnancy, this relation became null after controlling for adversity.…”
Section: Mental Health Outcomesmentioning
confidence: 91%
“…Higher PCEs also predicted less risky sexual behaviors (e.g., having sex with someone you do not know or trust; and reproductive planning (i.e., teenage, unwanted, or currently unplanned pregnancy; Merrick et al, 2020), but did not predict timing of sexual initiation . Higher PCEs predicted lower substance use in some studies Novilla et al, 2022), but not in others (Crandall et al, 2019Kuhar & Zager Kocjan, 2021;Miller et al, 2020;Rollins & Crandall, 2021;Anderson, 2021).…”
Section: Mental Health Outcomesmentioning
confidence: 94%
“…He is much more positive about his health and less susceptible to depression. It also shows great ability to adapt to situations [21]. In turn, coping strategies in the concept of Lazarus and Folkman show that people who are ready to fight the disease have a style focused on taking action.…”
Section: Coping With the Disease And Quality Of Life In Patients With Msmentioning
confidence: 99%
“…Personality and Place Attachment. Among many differences between introverts and extroverts, it has been well established that introverts and extroverts have different preferences in terms of stimulation from the surrounding environment (Miller et al, 2020;Yadegari and Alinaghi, 2020).…”
Section: Figurementioning
confidence: 99%